Automatic mechanism generation for pyrolysis of di-tert-butyl sulfide. Issue 31 (19th July 2016) - Class, Caleb A.; Liu, Mengjie; Vandeputte, Aäron G.; Green, William H.
Abstract : The automated Reaction Mechanism Generator (RMG), using rate parameters derived from ab initio CCSD(T) calculations, is used to build reaction networks for the thermal decomposition of di- tert -butyl sulfide. Abstract : The automated Reaction Mechanism Generator (RMG), using rate parameters derived from ab initio CCSD(T) calculations, is used to build reaction networks for the thermal decomposition of di- tert -butyl sulfide. Simulation results were compared with data from pyrolysis experiments with and without the addition of a cyclohexene inhibitor. Purely free-radical chemistry did not properly explain the reactivity of di- tert -butyl sulfide, as the previous experimental work showed that the sulfide decomposed via first-order kinetics in the presence and absence of the radical inhibitor. The concerted unimolecular decomposition of di- tert -butyl sulfide to form isobutene and tert -butyl thiol was found to be a key reaction in both cases, as it explained the first-order sulfide decomposition. The computer-generated kinetic model predictions quantitatively match most of the experimental data, but the model is apparently missing pathways for radical-induced decomposition of thiols to form elemental sulfur. Cyclohexene has a significant effect on the composition of the radical pool, and this led to dramatic changes in the resulting product distribution.